2017
DOI: 10.1017/s1047951116002754
|View full text |Cite
|
Sign up to set email alerts
|

Atrial septal defect with right-to-left shunt in the absence of pulmonary hypertension

Abstract: We describe the case of a 27-year-old gentleman who developed late-onset clubbing and cyanosis. Transoesophageal echocardiography revealed a 27-mm ostium secundum atrial septal defect and a large, floppy Eustachian valve directing right atrial blood to the left side of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Compared with the two-dimensional digital image, the three-dimensional model could more directly and comprehensively present the spatial information of the object, so the reconstructed three-dimensional model of the blood vessel was conductive to diagnosis of the disease better. Manuel et al (2017) showed in the study that most adult ASD patients had different degrees of TR, and patients with moderate to severe TR accounted for about 20% of the total number [14]. In this experiment, there were 12 patients with the amount of TR above 25 mL before the surgery, and there were no patients with the amount of TR higher than 50 mL.…”
Section: Discussionmentioning
confidence: 73%
“…Compared with the two-dimensional digital image, the three-dimensional model could more directly and comprehensively present the spatial information of the object, so the reconstructed three-dimensional model of the blood vessel was conductive to diagnosis of the disease better. Manuel et al (2017) showed in the study that most adult ASD patients had different degrees of TR, and patients with moderate to severe TR accounted for about 20% of the total number [14]. In this experiment, there were 12 patients with the amount of TR above 25 mL before the surgery, and there were no patients with the amount of TR higher than 50 mL.…”
Section: Discussionmentioning
confidence: 73%
“…There are reports of a floppy eustachian valve directing the flow from the inferior caval vein to the left atrium. [1][2][3] This has been described as early as in 1976. 10 The very first description of atrial septal defects with cyanosis dates from 1949, where Selzer and Lewis postulate functional drainage of systemic venous blood into the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…In very few case reports, the eustachian valve remains functional and even after birth divides systemic venous blood towards the left atrium. [1][2][3] Anatomical connections of systemic veins to the left atrium are rare. They lead to different degrees of cyanosis dependent on the amount of systemic venous blood mixing with the pulmonary venous retour.…”
mentioning
confidence: 99%